2008
DOI: 10.4049/jimmunol.180.9.6229
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid Dendritic Cells Are Activated by Toxoplasma gondii to Present Antigen and Produce Cytokines

Abstract: Infection with the parasite Toxoplasma gondii leads to the induction of a Th1-type response dominated by IFN-γ production and control of this pathogen. Cells of the innate immune system are essential in initiating this response both through the production of IL-12 as well as the presentation of parasite-derived Ags to MHC-restricted T cells. Although dendritic cells (DCs) have been implicated in these events, the contribution of individual DC populations remains unclear. Therefore, multiparameter flow cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
99
3
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 47 publications
3
99
3
1
Order By: Relevance
“…The RH⌬ku80⌬hxg, RH⌬ku80⌬plp1 strains were transfected with 50 g of the dsRed expression plasmid (46), linearized within the tub promoter, and cloned by limiting dilution. DsRed strains were maintained with chloramphenicol selection.…”
Section: Methodsmentioning
confidence: 99%
“…The RH⌬ku80⌬hxg, RH⌬ku80⌬plp1 strains were transfected with 50 g of the dsRed expression plasmid (46), linearized within the tub promoter, and cloned by limiting dilution. DsRed strains were maintained with chloramphenicol selection.…”
Section: Methodsmentioning
confidence: 99%
“…One alternative mechanism is that pDCs produce cytokines other than IFN-I that can be used to combat bacteria. Little attention has been paid to pDC cytokine production other than IFN-I, but pDCs do produce IL-12 (18,34), and pDCs deficient in IL-18 production are unable to stimulate IFN-g production in HSV infection (35). It will be important to look at the full gamut of cytokines produced by pDCs in response to infectious agents, especially IL-12 and IL-18, both of which have been shown to be important in controlling L. pneumophila infection (33,36).…”
Section: Discussionmentioning
confidence: 99%
“…pDCs also produce IFN-I when exposed to Borrelia burgdorferi in vitro (17). Finally, pDCs can activate CD4 T cells via Ag presentation and secretion of IL-12 in response to Toxoplasma gondii infection (18). As IFN-I may also be an effector molecule used in the clearance of intracellular bacterial infections, such as L. pneumophila, we studied the role of pDCs in a mouse model of L. pneumophila infection.…”
mentioning
confidence: 99%
“…Indeed, IL-12 is a major cytokine secreted in response to T. gondii by neutrophils 23 , macrophages 24 , plasmacytoid dendritic cells (pDCs) 25 , conventional dendritic cells (cDCs) 26 and the subset of cDCs expressing CD8 27 . Recently Mashayekhi et al have demonstrated the critical role of CD8+ DCs for activation of innate immunity through IL-12 production during T. gondii infection and have shown that CD8+ DCs are the only cells whose IL-12 production is required to control acute infection 28 .…”
Section: Introductionmentioning
confidence: 99%